An Integrated Community-Based Model for Chronic Disease Care in a Community in the Lower Southern Peninsular Thailand - Khunnikom, Prawit; Sunthonnon, Tawatchai; Sang-arun, Sirunya; Issarachote, Ussanee; Kongbua, Wasana; Saengchong, Jariwan (Journal of Population and Social Studies [JPSS], 2026)
Effective chronic disease management requires community-based approaches tailored to local contexts. This study sought to develop an integrated community-based model for chronic disease care in a community in the lower southern peninsular Thailand. It was a research and development (R&D) study consisting of three phases: Phase 1 identified situational factors through focus group discussions; Phase 2 produced a model validated by three experts using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument; and Phase 3 employed a one-group pretest-posttest design to implement the model and evaluate outcomes over three months. Key informants included 30 patients with non-communicable chronic diseases and 15 healthcare professionals. Data analysis used descriptive and inferential statistics, paired-samples t-test, and content analysis. The study found that the integrated community-based model for chronic disease management consisted of three main components. First, individual participation (focusing on shared goal setting and risk awareness); Second, interpersonal participation (involving peer support and structured information/feedback exchange); and finally, community participation (including positive motivation, community-based healthcare activities, and surveillance). The results show that after the patients were taken care of with the integrated community-based model for three months, the average HbA1C (glycated hemoglobin) levels among chronic disease patients had significantly decreased by 0.10 (95% CI [0.04–0.16]), and the average systolic blood pressure had significantly decreased by 4.70 mmHg (95% CI [2.32–7.07]). Chronic disease clinics in comparable rural settings can adopt this three-tiered participation structure within existing services, with village health volunteers and community groups recognized as partners in care.